On unified boundary conditions for improved predictions of near-wall turbulence - Jakirlic, S.; Jovanovic, Jovan (Journal of Fluid Mechanics, 2010)
A novel formulation of the wall boundary conditions relying on the asymptotic behaviour of the Taylor microscale λ and its relationship to the homogeneous part of the viscous dissipation rate of the kinetic energy of turbulence ∈h =5q2/λ2, applicable to near-wall turbulence, is examined. The linear dependence of λ on the wall distance in close proximity to the solid surface enables the wall-closest grid node to be positioned immediately below the edge of the viscous sublayer, leading to a substantial coarsening of the grid resolution. This approach provides bridging of a major portion of the viscous sublayer, higher grid flexibility and weaker sensitivity against the grid non-uniformities in the near-wall region. The performance of the proposed formulation was checked against available direct numerical simulation databases of complex wall-bounded flows featured by swirl and separation. © 2010 Cambridge University Press.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.onunif
Keywords: turbulence modelling; wall-bounded flows